“Prototipo de riego inteligente para invernaderos de rosas usando la técnica de redes neuronales” - Washington Bladimir, Cayambe Cajo (2021)
The resource of technology has become essential in the flower sector, however, in many rose production activities this factor is not taken into account. Any flower grower can have control manually, which allows to ensure the harvest, improve productivity, water consumption and finally the level of competition, however this process can be carried out in a systematic way in a more agile and efficient way. In greenhouses there are still irrigation systems that are not suitable for reducing water consumption and many are not systematized but manually. For this reason, the research project aims to develop a systematized irrigation prototype for water control in roses, applying an optimal amount and thus improving the use of the vital resource. Another additional point of this systematized irrigation process is to keep the plants hydrated and designate the adequate amount of water that can be applied, thus reducing the intervention of people and increasing yield, since the production of roses in greenhouses has different factors that influence their growth such as climatic conditions and these have a great impact on the care of a crop for the growth of roses. 7 Therefore, it was decided to apply artificial intelligence in irrigation because it helps improve precision and save water and nutrients. “The optimization in the use of water is one of the most evident applications of the implementation of innovative technology in the sector” [2]. Through RNA, it is sought to carry out an intelligent irrigation system which will be of great contribution to the research group of artificial intelligence techniques and will benefit the floricultural sector where it is the site for obtaining the respective data to subsequently execute an analysis and process. of the information obtained.